2023
DOI: 10.1111/xen.12799
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against hyaluronan oligosaccharides in xenotransplantation

Abstract: Carbohydrate‐specific antibodies are significant mediators of xenograft rejection. This study analyzed the carbohydrate specificity of antibodies in baboons before and after xenotransplantation of organs or injection of porcine red blood cells from hDAF transgenic pigs, using a glycan array with structurally defined glycans. Antibodies against hyaluronic acid disaccharide (HA2) showed the highest reactivity at baseline and rose after xenogeneic exposure. We also investigated in the serum of baboons that underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Using a 406-component CFG glycan microarray, Bello-Gil et al screened serum from baboons before and after receiving a red blood cell injection, heart xenotransplantation, or kidney xenotransplantation from transgenic pigs. 325 The authors identified numerous antibodies—each with a different glycan target—present at high levels before transplantation. Notably, many of these antibodies further increased in reactivity after transplant, with antibodies targeting the hyaluronan disaccharide showing the greatest increase relative to pre-transplant levels.…”
Section: Autoimmune Diseases Other Diseases and Other Applicationsmentioning
confidence: 99%
“…Using a 406-component CFG glycan microarray, Bello-Gil et al screened serum from baboons before and after receiving a red blood cell injection, heart xenotransplantation, or kidney xenotransplantation from transgenic pigs. 325 The authors identified numerous antibodies—each with a different glycan target—present at high levels before transplantation. Notably, many of these antibodies further increased in reactivity after transplant, with antibodies targeting the hyaluronan disaccharide showing the greatest increase relative to pre-transplant levels.…”
Section: Autoimmune Diseases Other Diseases and Other Applicationsmentioning
confidence: 99%
“…Natural and inducible anti-SDa plays important roles in GTKO pig-to-rhesus monkey xenotransplant rejection, thus providing further support for the notion that Gal and SDa antigens should be simultaneously targeted ( 35 ). Exploration of new key non-α-Gal antigens is currently underway ( 36 ).…”
Section: Key Xenoantigensmentioning
confidence: 99%